NEOGENE EVOLUTION OF AN ARCUATE STRUCTURE IN THE UMBRIA-MARCHE APENNINES (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
The Umbria-Marche Apennines is an arcuate fold and thrust belt, built up during Upper Miocene-Pliocene. Folds and thrusts affect at the surface the sedimentary cover. The AA. examine the innermost ridge in the sector between M. Nerone to the north and M. Serano to the south. lt is made up of a dextral en-échelon set of periclines, whose axial trend is NW-SE to the north and N-S (sometimes NNE-SSW) to the south. The en-échelon set of periclines is externally enveloped by a thrust, bent in piane view. As the basis of the Neogene evolution of the examined structure, the AA. propose two deformation episodes. In the first the development of frontal and oblique blind thrusts (affecting only the Calcare massiccio and Anidriti di Burano formations) are responsible for macrofolds and for their planimetrie distribution. The second one is due to NE thrusting along a thrust which probably reactivates the blind thrusts. In this moment of thrust the en-échelon set of periclines constitutes the hanging-wall of the thrust.
Keywords: Umbria-Marche Apennines; Structural Geology; Arcuate structure evolution.